Endogenous ligand of the APJ receptor Apelin-13 inhibits cell apoptosis and oxidative stress of cardiomyocytes: Protective effect of Apelin-13 on H9c2 cells - Jin, Hu; Cao, Longmeng; Tang, Dachao; Dai, Xiaochun (Cellular and Molecular Biology, 2023)
The present study aimed to investigate the effect of Apelin-13 on nicotine-induced injuries of cardiomyocytes. To establish an H9c2 cell model of nicotine-induced apoptosis, H9c2 cells were divided into the control group, nicotine group, and Apelin-13+nicotine group. The apoptosis rate of H9c2 cells was then detected by flow cytometry. Later, the expressions of indicators related to apoptosis, oxidative stress, and inflammatory responses were measured via Western blotting and quantitative real-time polymerase chain reaction (qRT-PCR). The results revealed that the expression of B-cell lymphoma-2 (Bcl-2) was remarkably down-regulated (P<0.01), while the apoptosis rate and the expressions of apoptosis-related proteins (Bcl-2-associated X protein (Bax) and cysteinyl aspartate specific proteinase-3 (Caspase-3)) were significantly up-regulated (P<0.01) in the nicotine group. However, the variation trends of Bcl-2, Bax, and Caspase-3 in the Apelin-13+nicotine group were contrary to those in the nicotine group (P<0.01). Additionally, the expressions of interleukin-1 beta (IL-1β) and tumor necrosis factor-alpha (TNF-α) obviously declined (P<0.01), while those of superoxide dismutase 1 (SOD1) and SOD2 dramatically rose in the Apelin-13+nicotine group (P<0.01). Furthermore, Apelin-13 treatment evidently elevated the expressions of phosphorylated protein kinase B (p-AKT) and phosphorylated phosphatidylinositol 3-kinase (PI3K). In conclusion, Apelin-13 inhibits nicotine-induced apoptosis and oxidative stress in H9c2 cells via the PI3K/AKT signaling pathway.